Inhibition of Sterol Biosynthesis in Chlorella sorokiniana by Triparanol - Chan, Jarvis T. (1974)
When Chlorella sorokiniana was cultured in the presence of 1 mg/1 triparanol succinate, there was a 42% reduction in total sterol concentration. Algal biomass was reduced by approximately the same amount. In addition to the cycloartenol, cyclolaudenol, 24-methyl-pollinastanol, ergosta-5, 7-dien-3β-ol, and ergosterol that occur in control culture, pollinastanol, 14α-methyl-5α-ergost-8-en-3β-ol, 5α-ergosta-8, 14, 22-trien-3β-ol, 5α-ergosta-8(14), 22-dien-3β-ol, 5α-ergosta-8(9), 22-dien-3β-ol, 5α-ergosta-8, 14-dien-3β-ol, 5α-ergost-8(9)-3n-3β-ol, 5α-ergost-8(14)-en-3β-ol, 5α-ergosta-7, 22-dien-3β-ol, and 5α-ergost-7-en-3β-ol were isolated and identified from triparanol succinate-treated cells. A biosynthetic pathway for sterol biosynthesis in this organism is postulated based on all the sterols that were isolated and identified in triparanol-treated cultures of C. sorokiniana. Cyclolaudenol appears to be the product of the first alkylation at C-24 in this organism rather than the more common 24-methylene cycloartanol. Since 24-methylene sterols are needed for the second alkylation reaction, this would explain the absence of C-29 sterols in C. sorokiniana. Four of the sterols identified in C. sorokiniana are reported for the first time in a living organism. They are: 24-methyl pollinastanol, 5α-ergosta-8, 14, 22-trien-3β-ol, 5α-ergosta-8(14), 22-dien-3β-ol and 5α-ergost-8(14)-en-3β-ol.